Perfil do administrador: a relevância do inglês dentre as competências do profissional de administração na perspectiva de recrutadores - Colares, Ana Beatriz Pereira (Brasil, 2024)
This study pertains to the theme of Competencies and aims to analyze the degree of importance of the English language among the various competencies required for administration professional needs to have to be inserted into the job market in Manaus. The methodological procedures employed were based on a qualitative approach through exploratory and descriptive research. Data collection involved standardized interviews with six questions conducted with recruiters who had over 4 years of experience in the field. Subsequently, the transcriptions of the interviews were subjected to content analysis to categorize the participants' responses. The main findings reveal that while English holds significance in the lives of business administrative professionals, prior experiences carry greater weight in hiring decisions than language proficiency. Additionally, the study identified key competencies among participants, including teamwork, communication, continuous learning, with a notable mention of resilience. Notably, resilience was mentioned by interviewees with extensive experience in the field and one with an academic background in psychology, a competency not found in the reviewed literature. This finding is remarkable as it was cited by professionals with distinct profiles in terms of experience and academic background compared to the other participants.